Role of virus infection in asthma 2 - Johnston, Sebastian (Henry Stewart Talks, 2011)
Role of viruses in development of asthma, Association between early life severe lower respiratory viral illness and later development of asthma, Is this association due to a common risk factor, a causal factor, or both?, Future studies
Updated at 2014/10/13